2015
DOI: 10.1515/bvip-2015-0071
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Coxiella burnetii in Polish cattle herds

Abstract: The aim of the study was to assess the seroprevalence of Coxiella burnetii in cattle herds in different regions of Poland. A total of 1150 serum samples collected from 443 cattle herds from 14 provinces were tested using complement fixation test. The seroprevalence was different in individual regions of Poland. The average percentage of seropositive herds was 40.41% and these herds were identified in each province tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…The estimated prevalence of Q fever in Latvian dairy cows is close to the 8% herd level prevalence reported for Sweden [32] and considerably lower than the herd level prevalence reported in countries of western Europe (82% in The Netherlands [18], 79% in Denmark [16], 72% in Germany [33] or 70% in Spain [34]) or central Europe (40% in Poland [35]). Other countries of northern Europe have reported even lower levels of prevalence in dairy cattle herds -0% in Norway [36] and 0•24% in Finland [37] suggesting that in northern Europe C. burnetii infections of dairy cattle are significantly less common as opposed to western and central Europe.…”
Section: Discussionsupporting
confidence: 43%
“…The estimated prevalence of Q fever in Latvian dairy cows is close to the 8% herd level prevalence reported for Sweden [32] and considerably lower than the herd level prevalence reported in countries of western Europe (82% in The Netherlands [18], 79% in Denmark [16], 72% in Germany [33] or 70% in Spain [34]) or central Europe (40% in Poland [35]). Other countries of northern Europe have reported even lower levels of prevalence in dairy cattle herds -0% in Norway [36] and 0•24% in Finland [37] suggesting that in northern Europe C. burnetii infections of dairy cattle are significantly less common as opposed to western and central Europe.…”
Section: Discussionsupporting
confidence: 43%
“…Therefore, it is not surprising that cattle were the primary source of the Q fever outbreaks in Poland, whereas in general, the small ruminants are considered to be the main source of infection for humans (Chmielewski and Tylewska-Wierzbanowska, 2013). The seroprevalence among cattle herds in this study was significantly lower than reported in the previous survey (Jodełko et al, 2015) when samples were tested by CFT (Siemens Healthcare, Germany). The cause of decrease of seroprevalence has not yet been determined, but we speculate that it may be related to differences in diagnostic method.…”
Section: Discussioncontrasting
confidence: 57%
“…Also in Poland a serological monitoring programme for cattle and small ruminants has been implemented [9] since 2010. According to recently published data, herd-level seroprevalence in Polish cattle was estimated at 40.41%, which corresponds with European averages [10]. However, there is lack of information about current prevalence of C .…”
Section: Introductionmentioning
confidence: 99%